Medication Supportive Behavior of Mothers with Children with ADHD: A Structural Equation Model (Medico Legal Update, 2020)
Background/Objectives: This study aimed to establish and validate a supportive behavior model for the medication of mothers with children with ADHD based on Theory of Planned Behavior (TPB) and empirical evidence.Method/Statistical Analysis: Participants were 205 mothers with children in elementary school in grades 1 to 3 who had been diagnosed with ADHD and experienced medication treatment. A constructed Structural Equation Model (SEM) was analyzed using AMOS program.Findings: The goodness-of-fit index of the final model was found to be appropriate. The model’s explanatory power for mother’s medication supportive behavior was 90.4%. The intention for medication supportive behavior (? = .486, p